Contemporary social problems and the diversity of violent crime - Houria Benhamza; Fatma Ghai (Social Empowerment Journal, 2020)
The violence as a social phenomenon with political, economic and cultural dimensions lead us to the question of the intertwining concepts, their complexity and their differences from one society to another, and also to the complexity of methods of controlling them in social systems and norms and in the international laws and decrees and laws, as for our reasons in our view, the enormous development in Economic production, diversification of goods, openness of markets, freedom of trade, and infinity in economic laboratories and the development of information systems are among the most important reasons that led to the emergence of many social problems in recent times that were a major factor in the spread of violent crime.